The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5194/isprs-annals-iv-2-w2-99-2017
|View full text |Cite
|
Sign up to set email alerts
|

Line-Drawing Enhanced Interactive Mural Restoration For Dunhuang Mogao Grottoes

Abstract: ABSTRACT:Dunhuang Mogao Grottoes in western China is one of the most famous World Cultural Heritage Sites, known for its glorious Chinese Buddhist art spanning a period of 1,000 years. However, it has been suffering from damage and degradation caused by man-made and natural factors. In this article, we present a novel line-drawing enhanced interactive system for digital restoration of damaged murals in Mogao Grottoes. Our system consists of four components, namely data pre-processing, damaged area selection, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The results show that the damaged murals can be repaired better by using the repair model in this study. By comparing the model constructed in this study with the method in Fu et al, 12 the predicted value of the repair model in this study is closer to the true value. Moreover, in the similarity rate, by comparing the number of training samples with the difference of smoothing parameter d, it is found that when the value of d is small, the number of training samples should be increased to promote the accuracy of the prediction value.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The results show that the damaged murals can be repaired better by using the repair model in this study. By comparing the model constructed in this study with the method in Fu et al, 12 the predicted value of the repair model in this study is closer to the true value. Moreover, in the similarity rate, by comparing the number of training samples with the difference of smoothing parameter d, it is found that when the value of d is small, the number of training samples should be increased to promote the accuracy of the prediction value.…”
Section: Discussionmentioning
confidence: 50%
“…Although the repair model constructed in this study is superior to the method in literature, 12 it takes a long time to implement the efficiency, which is due to the time spent in collecting similar sample materials. By choosing the parameters of the smoothing operator in this study, the influence of the smoothing operator on the predicted value is judged by the step size of 0.01, as shown in Figure 7.…”
Section: Repair Process Of Dunhuang Muralsmentioning
confidence: 97%
See 1 more Smart Citation
“…The Dunhuang murals are of great research value, especially for the study of religion, class relations, costumes, architecture and humanistic tales from different periods (such as Zhang Qian's Diplomatic Missions [张骞出使西域]) (Hu, 1993). In past research studies, taking the Dunhuang murals as objects of restoration, the role of digital repair combined with deep learning algorithms in the mural restoration was explored (She, 2020), and the line-drawing enhanced interactive system for the Dunhuang mural restoration was built (Fu et al, 2017). An improved inpainting algorithm for repairing the Dunhuang murals was proposed, and it obtained good visual effects, as well as improved objective evaluation EL 40,3 values, such as the peak signal-to-noise ratio of the image (Chen et al, 2020a(Chen et al, , 2020b.…”
Section: Literature Review 21 Dunhuang Cultural Heritagementioning
confidence: 99%
“…Gao [46] proposed a virtual restoration method based on minimum spanning trees to restore mural color. Fu et al [47] proposed a novel enhanced white-out interactive system for mural image restoration. Zhou et al [48] proposed an intelligent restoration technique for digital images of murals based on machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%